2019
DOI: 10.5606/archrheumatol.2019.7160
|View full text |Cite
|
Sign up to set email alerts
|

Can Fear of Movement, Depression and Functional Performance be a Predictor of Physical Activity Level in Patients With Knee Osteoarthritis?

Abstract: Objectives: This study aims to explore whether fear of movement, depression and functional performance are predictors of physical activity levels in patients with knee osteoarthritis (OA). Patients and methods: A total of 200 patients (80 males, 120 females; mean age 53.23±5.99 years; range, 40 to 65 years) with knee OA participated in this cross-sectional, correlational-design study. Oxford Knee Score (OKS) was used to evaluate physical function and pain through patient perspective. Six-Minute Walk Test (6-MW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…In another study designed to examine whether fear of movement, depression and functional performance are predictors of physical activity level in cases with knee osteoarthritis, Kilinç et al 21 who studied 200 cases concluded it is important to improve physical activity levels in this group early on before the disease progresses and becomes more costly to treat. But the actual cause of the fear and what should be done was unclear, although Selcuk et al 19 mention that simply focusing on pain relief is probably insufficient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study designed to examine whether fear of movement, depression and functional performance are predictors of physical activity level in cases with knee osteoarthritis, Kilinç et al 21 who studied 200 cases concluded it is important to improve physical activity levels in this group early on before the disease progresses and becomes more costly to treat. But the actual cause of the fear and what should be done was unclear, although Selcuk et al 19 mention that simply focusing on pain relief is probably insufficient.…”
Section: Resultsmentioning
confidence: 99%
“…28 Another is the self-management and exercise approach discussed by Jonsson et al 48 and that might include efforts to foster skills mastery, falls, pain coping, and self-efficacy/positive beliefs. 49 Others that have been proposed and need to be examined empirically in well-designed trials include: aquatic exercises, 50 brain targeted treatments, 51 joint protection/general education, 20,24,52,53 approaches that increase physical activity, 19,21,38 Tai Chi, 54 and guided imagery, drawings, and education. 24 Web based osteoarthritis interventions and others that aim to reduce fears 34,55 and that might consider proving information on medication safety, exercise safety, home modifications, and injury prevention may also prove highly practical and efficacious for selected cases.…”
Section: Resultsmentioning
confidence: 99%
“…diz OA'lı bireylerde fiziksel aktivite düzeyini etkileyen parametreleri inceledikleri çalışmada; kinezyofobi, depresyon ve fonksiyonel performansın fiziksel aktivite düzeyi ile orta düzeyde negatif yönde ilişkili olduğunu bulmuşlardır. 27 Alshahrani ve ark. diz OA'lı bireylerde kinezyofobi ile diz ağrısı şiddeti, eklem pozisyon hissi ve fonksiyonel performans arasındaki ilişki inceledikleri çalışmalarında, kinezyofobi ile ağrı ve 5 kez otur kalk test performansı arasında pozitif yönde orta düzeyde ilişki olduğunu bulmuşlardır.…”
Section: Discussionunclassified
“…[31] Also, Kilinc et al also reported similar results showing a significant relationship between the level of activity and kinesiophobia and fear of movement can be an important predictor for the level of physical activity. [32] Domenech et al reported that kinesiophobia significantly correlated with pain and disability in anterior knee pain. [33]…”
Section: Discussionmentioning
confidence: 99%